Back Cover Image, Volume 4, Number 6, November 2022. Issue 6 (29th November 2022) - Hu, Zhengqiang; Zhang, Fengling; Liang, Huanyu; Zhang, Hao; Wang, Huaizhi; Wang, Tiansheng; Liu, Renbin; Liu, Jie; Li, Yadong; Dong, Xiaotong; Bao, Lianyu; Liang, Zhuan; et al.
Abstract : Back cover image : Iron fluoride demonstrates high operational voltages and high specific capacities, offering high energy densities for lithium‐ion batteries. However, the debate of their electrochemical reaction mechanisms limits further development, and in article number 10.1002/cey2.201, Hong S. Li et al. employ advanced in situ magnetometry to detect their intrinsic electronic structure during cycling, reveal charge storage behavior in FeF2 cathode and provide important references for designing energy storage devices based on spin‐polarized surface capacitance.